A newly discovered Iron Age site at Sarrez, Iranian Kurdistan - Amelirad, Shelir; Razmpoush, Abbas (Ancient Near Eastern studies, 2015)
Sarrez is an ancient site in Kurdistan Province, Iran, near the present-day country town of Kamyaran. This site was discovered accidentally during dam construction activities. It has yielded some metal artefacts, potsherds and bones that are comparable to Iron Age III instances. The collection in its entirety is discussed in this article. One of the main objects from Sarrez is a decorated beaker with a scene on its wall that is comparable in many ways to examples of Neo-Assyrian art. The purpose of this paper is to publish and date the metal objects of the Sarrez collection based on this bronze beaker, which is one the few beakers from western Iran which has been found in a secure context.
Gesehen am 16.08.2024